Romani : a linguistic introduction - Matras, Yaron, 1963- (Cambridge University Press, 2002)
Romani, the language spoken by over 3.5 million Gypsies, has recently attracted increasing interest from both scholars and language policy makers. This book is the first overview in English of the structure, history, typology and dialects of Romani. It provides an essential reference for anyone interested in this fascinating language.